Essays on Financial Frictions in Lending Markets - Stine Louise Daetz (Copenhagen Business School (CBS), 2018)
The first essay shows that corporate bond issuers derive value from bond underwriter relationship capital. A strong underwriter relationship enables the underwriter to credibly certify the issuer on the bond market which is fundamental for firms when issuing new debt and refinancing maturing debt. In order to empirically verify this certification hypothesis we study corporate bond issuing firms' underwriter relations and analyze their value for the issuing firm. The second essay provides a detailed investigation of the implications of creditors' use of credit default swaps (CDSs) for the debt financing of related firms. CDSs are financial derivatives that protect the buyer against default of a given reference firm. The availability of CDS contracts has in general been outlined to improve bank lending by reducing financial frictions on the supply side of credit. Using unique and comprehensive CDS and credit registry data from Deutsche Bundesbank I explicitly study the CDS holdings of banks with a credit relationship to the reference firm and analyze the role of the variation in creditors use of CDSs for the borrower's debt financing. As outlined in the data creditors typically hold multiple CDSs written on the same firm and are often also net sellers of CDS contracts written on their own borrowers. The third essay investigates whether unconventional monetary interventions by central banks can stimulate corporate investment and, thus, afiect the real economy. Specifically, we address this question by analyzing ECB's three-year Longer-term Refinancing Operations (LTROs) as of 2011-2012. The LTROs were large liquidity injections that were implemented to support the real economic recovery after the European Sovereign Debt Crisis and provided cheap funding to Eurozone banks. For the empirical investigation of the impact of such liquidity interventions, we make use of comprehensive data on banks' use of the LTRO funds and Eurozone non-financial corporations' investment policies around the LTRO implementation.
hdl:10398/9654
Keywords: 650